Результати експериментальних досліджень біотермічних процесів компостування підстилкового посліду на основі лушпиння соняшнику в натурних буртах - Павленко, С. І.; Павленко, С. И.; Pavlenko, S. (ЦНТУ, 2017)
Втрати поживних біогенних речовин підстилкового посліду пов’язані з фізико-хімічними і мікробіологічними процесами, які відбуваються безпосередньо після виділення екскрементів тваринами, а також під час накопичення, зберігання і перероблення. Під впливом механізованих втручань та біоконверсних перетворень відбуваються зміни в масовому балансі біогенних компонентів тваринницьких відходів та в біоенергетичному потенціалі. Мета – дослідження технологічних процесів прискореного біотермічного компостування підстилкового посліду на основі лушпиння соняшнику технічними засобами механізованого компостування. Методи і прийоми досліджень: метод натурних спостережень, методи планування експерименту, методики тепловізерних і пірометричних спостережень, електротехнічні прийоми визначення динаміки зміни температури. Динаміка температур у буртах досліджувалася з використанням персонального комп’ютера до якого підключався електронний термометр TM-32/H-5T із системою температурних зондів на основі датчиків температури DS18B20. Температурне поле поверхні або розрізу буртів визначалося з використанням тепловізора Testo-875, який дозволяє проводити аналіз температурних полів із абсолютною похибкою вимірювання 0,01 °С. В результаті дослідження отримана динаміка зміни температури в кожній точці натурного бурта згідно розробленої методики. Потери питательных биогенных веществ подстилочного помета связанные с физико-химическим и микробиологическим процессами, которые происходят непосредственно после выделения экскрементов животных, а также во время накопления, хранения и переработки. Под влиянием механизированных вмешательств и биоконверсных преобразований происходят изменения в массовом балансе биогенных компонентов животноводческих отходов и в биоэнергетическом потенциале. Цель - исследование технологических процессов ускоренного биотермического компостирования подстилочного помета на основе шелухи подсолнечника техническими средствами механизированного компостирования. Методы и приемы исследований: метод натурных наблюдений, методы планирования эксперимента, методики тепловизерних и пирометрических наблюдений, электротехнические приемы определения динамики изменения температуры. Динамика температур в буртах исследовалась с использованием персонального компьютера к которому подключался электронный термометр TM-32 / H-5T с системой температурных зондов на основе датчиков температуры DS18B20. Температурное поле поверхности или разреза буртов определялось с использованием тепловизора Testo-875, который позволяет проводить анализ температурных полей с абсолютной погрешностью измерения 0,01 ° С. В результате исследования получена динамика изменения температуры в каждой точке натурного бурта согласно разработанной методики. Loss of nutrient nutrients of litter litter is associated with physico-chemical and microbiological processes that occur immediately after the excrement of animals, as well as during accumulation, storage and processing. Under the influence of mechanized interventions and bioconversal transformations, changes in the mass balance of nutrient components of livestock wastes and in bioenergy potential are taking place. The purpose is to study the technological processes of accelerated biodegradation composting of litter litter based on sunflower husk by technical means of mechanized composting. Methods and techniques of research: method of field observations, methods of planning the experiment, methods of thermal and pyrometric observations, electrotechnical methods of determining the dynamics of temperature change. The temperature dynamics in the booths was studied using a personal computer to which an electronic thermometer TM-32 / H-5T with a temperature sensor system based on DS18B20 temperature sensors was connected. The temperature field of the surface or the cut of burs was determined using the thermo-testor Testo-875, which allows the analysis of temperature fields with an absolute measurement error of 0.01 ° C. As a result of the study, the dynamics of temperature variation at each point of the bourse according to the developed method is obtained. The results of researches showed that mechanical abrasion of raw materials - aeration, provides growth of internal temperatures - 7 points of measurement on the height of the port H1 = 1.5 m to a maximum temperature of 65-71 ° C and up to 50-58 ° C at the height of the port H2 = 1, 0 m for 2-3 days after packing of the bouquet. At 15-17 days, the temperature drops to 50 ° C, which does not correspond to the thermophilic mode of bacterial activity, and the processes go to the mesophilic regime - up to 40 ° C. Humidification - up to 20% of the mass of the broom and aeration - effective technological techniques that provide temperature maintenance of the corresponding thermophilic regime 3-5 days more without using them.
Результаты экспериментальных исследований биотермического процесса компостирования подстилочного помета на основе лузги подсолнечника в натурных буртах
Results of experimental researches of biotermic processes of composition of surface positions on the basis of suspending of sunflower in natural burtazes
Keywords: послід; компост; бурт; температура; біотермічний процес; помет; биотермический процесс; litter; compost; burt; temperature; biothermic process